Development Planning for Reclamation of Godbless Park Beach as A Public Space in Manado City - Patriani Wilma Eunike Supit; Soesilo Zauhar; Siswidiyanto Siswidiyanto (Indonesian Journal of Environment and Sustainable Development, 2019)
This research aimed to describe and analyse the development planning of the Godbless Park Beach Reclamation Area as a Public Space in Manado City. This qualitative research is descriptive analysis and the data collection techniques are semi-structured interviews and documentation study.  Then, they were analysed using interactive model. It was found that the development planning process of the Reclamation Area of Godbless Park Beach as a Public Space in Manado City has not been structured systematically, comprehensively and sustainably. This is due to various obstacles, namely overlapping regulations, the implementation of goals and targets that are not as expected, inappropriate setting of locations and times, lack of fund allocation, and human resources that are not in accordance with their respective basic tasks and functions.  In addition, the construction of the Reclamation Area of Godbless Park Beach as a Public Space has not had a positive impact on the surrounding environment in Manado City.